Implementation of Management Information System 5.0 and its Impact on Employee Performance in Public Services - Umar, Syarif; Zacharias, Tehubijuluw; Selanno, Henry (Syntax Literate, 2024)
This study aims to analyze the implementation of management information system 5.0 and its influence on employee performance in public services at the Communication and Informatics Office of West Seram Regency. This study uses a descriptive-quantitative approach with a causal correlation type. The population used in this study were all employees of the Communication and Informatics Office of West Seram Regency totaling 39 people. Determination of the number of saturated samples. Data were analyzed using multiple linear regression. The results of the study concluded that (1) System Quality does not have a significant effect on public service performance (2) Information quality does not have a significant effect on service performance (3) Service quality has a significant effect on public service performance; (4) System Quality, information quality and service quality have a significant effect simultaneously on public service performance.